Household cost of accessing contraceptive services among women in Urban communities in Ghana - Caesar Kaba Kogoziga; Desmond Dzidzornu Otoo; Raphael Kwasi Gborgbortsi; Richmond Owusu; Serwaa Akoto Bawua (PLoS ONE, 2025)
Background In many developing nations, including Ghana, access to contraceptive services, remains a critical concern where urban areas face unique challenges in healthcare delivery. Despite various interventions, the financial burden of assessing these contraceptive services continues to hinder adoption by women especially those with economic challenges. This study explored the costs incurred by women seeking contraceptive services in urban communities by estimating the direct, indirect, and intangible costs in Ghana. Methods A facility-based cross-sectional study was conducted using the patient perspective; to gather data on direct medical and non-medical costs, indirect costs and intangible costs that were associated with women seeking contraceptive services. A structured questionnaire was used to collect data from three Planned Parenthood Association of Ghana (PPAG) facilities in the Accra metropolitan, Suame municipal and Sagnarigu districts in the Greater Accra, Ashanti, and Northern Regions respectively. A total of 125 women accessing contraceptive services were randomly selected and included in the study. Data was analyzed descriptively and reported in frequency tables, pie, and bar charts. All costs were reported in Ghana Cedi and US dollar. Results The average direct cost of contraceptive services was GHS 18.37 ± 22.11 (US$ 1.53 ± 1.84) per visit. This comprised an average direct medical cost of GHS 8.50 ± 7.18 (US$ 0.71 ± 0.60) and non-medical cost of GHS 9.84 ± 20.23 (US$ 0.82 ± 1.69). Clients, on average, lost 52.1 minutes due to traveling and waiting, resulting in an average productivity loss of GHS 1.62 per visit. The average economic cost of contraceptive service was GHS 19.99 (US$ 1.67) per patient. About 92% of the economic cost was made up of direct cost. 71.2% of respondents consulted their partners before accessing contraceptive services, and 94% believed that their decision to use contraceptives did not negatively affect their relationships, however, many reported pains during the procedure. Conclusion The study highlights the considerable direct and indirect costs associated with accessing modern contraceptive services, indicating a potential barrier to access when compared to daily minimum wage and prevailing economic conditions. Addressing these economic challenges is crucial for ensuring access to contraceptive services. Innovative strategies such as service delivery outreaches and deployment of digital health interventions to expand self-care is recommended to help reduce travel time to and from the service delivery point for contraceptive services.